New Insights into the Catalytic Activity of Cobalt Orthophosphate Co3(PO4)2 from Charge Density Analysis. Issue 69 (8th November 2019) - Keil, Helena; Hellström, Matti; Stückl, Claudia; Herbst‐Irmer, Regine; Behler, Jörg; Stalke, Dietmar
Abstract: An extensive characterization of Co3 (PO4 )2 was performed by topological analysis according to Bader's Quantum Theory of Atoms in Molecules from the experimentally and theoretically determined electron density. This study sheds light on the reactivity of cobalt orthophosphate as a solid‐state heterogeneous oxidative‐dehydration and ‐dehydrogenation catalyst. Various faces of the bulk catalyst were identified as possible reactive sites given their topological properties. The charge accumulations and depletions around the two independent five‐ and sixfold‐coordinated cobalt atoms, found in the topological analysis, are correlated to the orientation and population of the d‐orbitals. It is shown that the (011) face has the best structural features for catalysis. Fivefold‐coordinated ions in close proximity to advantageously oriented vacant coordination sites and electron depletions suit the oxygen lone pairs of the reactant, mainly for chemisorption. This is confirmed both from the multipole refinement as well as from density functional theory calculations. Nearby basic phosphate ions are readily available for C−H activation. Abstract : How to Cat : The experimental and theoretical topological analysis of the electron density distribution in Co3 (PO4 )2 identified the (011) face to be best suited for catalysis. Fivefold‐coordinated Co ions in close proximity to advantageously oriented electron‐depletion sites suit the reactant's oxygen lone pairs most for chemisorption and heterogeneous C−H activation.